Fertility and pregnancy issues in BRCA-mutated breast cancer patients. (September 2017) - Lambertini, Matteo; Goldrat, Oranite; Toss, Angela; Azim, Hatem A.; Peccatori, Fedro A.; Ignatiadis, Michail; Del Mastro, Lucia; Demeestere, Isabelle
Highlights: Fertility and pregnancy-related issues are one of the main areas of concerns for young women with breast cancer. Carrying a germline deleterious BRCA mutation adds additional burden on this regard. Specific needs and issues should be considered when counseling BRCA -mutated breast cancer patients. Reproduction studies in BRCA -mutated breast cancer patients should be considered a research priority. Abstract: Fertility and pregnancy-related issues represent one of the main areas of concerns for young women with breast cancer. Carrying a germline deleterious BRCA mutation adds additional burden on this regard due to the specific issues that should be considered during the oncofertility counseling of this special patient group. Despite the availability of a growing amount of data in the general breast cancer population on the feasibility and safety of fertility preservation and pregnancy after diagnosis, numerous challenges remain for BRCA -mutated breast cancer patients in whom very limited studies have been performed so far. Therefore, studies aiming to address the specific issues of these patients, including the impact of the mutation on their fertility potential, the safety and efficacy of the different strategies for fertility preservation, and the feasibility of having a pregnancy after diagnosis, should be considered a research priority. The aim of the present manuscript is to perform an in depth overview on the role of BRCA mutations in breast cancer with a specific focus on their impact on reproductive potential, and to discuss the fertility and pregnancy issues faced by BRCA -mutated breast cancer patients. The final goal of this manuscript is to highlight current and upcoming knowledge in this field for trying to help physicians dealing with these patients during oncofertility counseling.